Բողոքի անուղղակի արտահայտման լեզվական առանձնահատկությունները հայերեն համացանցային խոսույթում - Եղիազարյան, Գայանե; Ավետիսյան, Աննա (ԱԵԳՄՄ հրատ.)
The aim of the article is to define the levels of complaint indirectness and investigate the linguistic means of indirect complaint expression within Armenian Internet discourse. The study not only scrutinizes the diverse types of complaints but also delves into the linguistic means for their indirect expression. The topicality of this article arises from the prevailing tendency to voice complaints indirectly in Internet discourse and its potential influence on users. The selection of linguistic analysis methods is justified by the nature of the studied material and the aim of the research. The examination of the material was carried out through linguistic descriptive analysis. The research findings led us to conclude that the users express their complaints based on the scale of the indirectness levels suggested by J. House and G. Kasper. A number of linguistic means play a pivotal role in the skilful implementation of indirect complaint expression. Notably, lexical and phrasal units with negative connotations that are typical of the colloquial speech, along with the frequent use of negative constructions and indirect questions, are prominent in this regard. Additionally, diverse punctuation marks are employed in complaints to add subtlety to indirect complaint expressions, with sarcasm being a commonly observed characteristic in such instances. Целью данной статьи является определение уровней косвенности жалобы и исследование языковыx особенностей косвенного выражения жалоб в армянском интернет-дискурсе. В ходе исследования мы не только тщательно анализируем различные виды жалоб, но также всесторонне изучаем языковые средства, используемые для косвенного выражения жалоб. Актуальность данного исследования обусловлена приоритетом косвенных способов выражения жалоб в интернет-дискурсе и важностью изучения их воздействия на пользователей. Выбор методов лингвистического анализа обусловлен характером изучаемого материала и целью исследования. Исследование материала проводилось с использованием методов описательного анализа. Результаты исследования позволили нам сделать вывод о том, что пользователи выражают жалобы, основываясь на шкале уровней косвенности, предложенной Дж. Хаусом и Г. Каспером. Ряд языковых средств играет ключевую роль в грамотном использовании косвенного выражения жалобы. Примечательно, что в этом отношении выделяются лексические и фразовые единицы с негативной коннотацией и характерные для повседневно-разговорного стиля негативные конструкции, а также косвенные вопросы.
Keywords: Լեզվաբանություն